2010
DOI: 10.3892/ijmm_00000487
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress parameters in paediatric non-alcoholic fatty liver disease

Abstract: Abstract.We have investigated the presence and the possible clinical implications of oxidative stress in children with nonalcoholic fatty liver disease (NAFLD). The present study was an observational study of oxidative stress parameters in the progression of paediatric NAFLD. We observed the role of oxidative stress in children diagnosed with NAFLD by evaluating: serum protein carbonyls, hepatic expression of 8-hydroxy-2-deoxyguanosine (8-OHG), and circulating antibody against malondialdehyde adducted human se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 37 publications
4
58
0
Order By: Relevance
“…Hepatic oxidative injury was associated with the development of antibodies toward protein-adducted MDA in a significant proportion of children with NAFLD (63%) and in ~40% of adult patients with NAFLD (25). In a previous study, plasma NO and plasma MDA levels were significantly higher, and plasma vitamin E and C levels were significantly lower in patients with NASH than in those with NAFL (29).…”
Section: Köroğlu Et Al Oxidative Stress and Insulin Resistance In Nomentioning
confidence: 98%
See 1 more Smart Citation
“…Hepatic oxidative injury was associated with the development of antibodies toward protein-adducted MDA in a significant proportion of children with NAFLD (63%) and in ~40% of adult patients with NAFLD (25). In a previous study, plasma NO and plasma MDA levels were significantly higher, and plasma vitamin E and C levels were significantly lower in patients with NASH than in those with NAFL (29).…”
Section: Köroğlu Et Al Oxidative Stress and Insulin Resistance In Nomentioning
confidence: 98%
“…Depletion of GH, a major cellular antioxidant, has been reported in NAFLD (25). Leach et al (16) recently demonstrated that NASH was an independent predictor of decreased GH levels and patients with NASH had significantly lower levels of antioxidants.…”
Section: Köroğlu Et Al Oxidative Stress and Insulin Resistance In Nomentioning
confidence: 99%
“…CD4 + Th cells assist B-cells and CD8 + cytotoxic cells in the activation and perpetuation of immune and autoimmune reactions [12]. Consistently, IgG against antigens originating from oxidative stress products are detectable in NAFLD/NASH patients [13,14] and immunization of mice with lipid peroxidation products exacerbated NASH development [10]. Inflammation is a main pathological feature of NASH, and cells of adaptive immunity, along with cells of innate immunity, can trigger and sustain hepatic inflammatory reactions [12].…”
mentioning
confidence: 90%
“…27 The urinary psi levels mainly originate from ribosomal and transfer RNA degradation, reflecting RNA turnover 28 and hence protein turnover, as recently reported. [29][30][31] Actually, these metabolic incomes could be increased by oxidative modifications occurring in pediatric NAFLD, [32][33] including high dietary energy intake. 33 It is now well recognized that, in humans, NAFLD is associated with increased IP and small intestinal bacterial overgrowth, and these factors are associated with the severity of the liver tissue damage.…”
Section: Discussionmentioning
confidence: 99%